Reversal modes and magnetostatic interactions in Fe3O4/ZrO2/Fe3O4 multilayer nanotubes - Pitzschel, Kristina; Bachmann, Julien; Montero-Moreno, Josep M.; Escrig, Juan; Goerlitz, Detlef; Nielsch, Kornelius (Nanotechnology, 2012)
Reversal modes and magnetostatic interactions of multilayered Fe3O4/ZrO2/Fe3O4 nanotubes consisting of a ferromagnetic internal tube, an intermediate non-magnetic spacer and an external magnetic shell are investigated as a function of their geometric parameters and compared with those produced inside the pores of anodic alumina membranes by atomic layer deposition. Based on a continuum approach we obtained analytical expressions that underline the first experimental results and support their interpretation that the system of multilayer tubes behaves as the reversal of two isolated systems. It is observed that the magnetostatic interaction between both phases depends on the magnetic configurations in each phase and also on the geometrical parameters considered. These structures have potential applications in novel spintronics devices, ultra-small magnetic media and other nano-devices.